DEVELOPMENT OF INTERACTIVE WORDWALL AND VIDEO COMBINED-MEDIA TO IMPROVE ELEMENTARY STUDENTS' LEARNING OUTCOMES - Rusdi, Wardati Khumairah; Parapat, Humaidah Fatimah; Efendi, Salman Alparisi; Misman (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Disruption in the world of education today encourages educators to innovate and foster high creativity to create enjoyable learning processes. The fundamental problems faced include the use of conventional learning media, the lack of enjoyable game-based learning media in elementary schools, and students' difficulties in mathematics. This research has two objectives: (1) to produce Wordwall learning media, and (2) to determine the validity, practicality, and effectiveness of Wordwall media on the theme of weather. This research uses the ADDIE paradigm, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects are the 3rd-grade students of SDIT Nurul Ilmi, and the object is the developed learning media. The research findings are as follows: (1) the product produced is Wordwall, an educational wordwall game based on a website presented in the form of a link combined with a video, (2) the Wordwall learning media has met the validity criteria (material expert validation of 96.99% and media expert validation of 88.57%), practicality (scoring 91.67%), and effectiveness (scoring 71,36%). The developed Wordwall learning media has met the aspects of validity, practicality, and effectiveness, and is intended for educators to use this media for students in the design, development, implementation, and evaluation classes. The subjects of the research are third-grade students on the theme of weather